Homocysteine Level in the Blood and Follicular Fluid is Higher in Infertile Women with Endometriosis - Natadisastra, Muharam (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To compare and determine the differences in the level of homocysteine in the blood and follicular fluid in infertile women with and without endometriosis, then analyze the effect of homocysteine levels to oocyte quality. Methods: This study was cross-sectional study. Fifty-nine subjects following the in-vitro fertilization program are included in the admission criteria were divided into two equal groups, ie groups of endometriosis and without endometriosis consecutively (consecutive sampling). Each subject taken from the blood and follicular fluid then measured the levels of homocystein levels with immuoassay method. The mean of each group was statistically tested with an independent t test. Result: The mean levels of homocysteine in the blood is higher in the endometriosis group than without endometriosis group and it was statistically significance (8.34 ± 2.68 vs 6.71 ± 1.56, p=0.007; 95% CI: 0.02417-0.14657). Similarly, the levels of homocysteine in follicular fluid , the endometriosis group is higher and statistically significance (6.19 ± 1.67 vs 3.46 ± 1.03; p= 0.000; 95% CI: 0.19310-0.32353). All oocytes are in good quality in both groups, maturation grade 3. There is a correlation between the levels of homocysteine in the blood and follicular fluid in the endometriosis group and assessed with Pearson test, and it found significant (p = 0.002) and the correlation value 0.553 (moderate correlation strength) and direction of a positive correlation. Conclusion: The mean levels of homocysteine in the blood and follicular fluid in infertile women with endometriosis is higher than without endometriosis and were statistically significantly different. These homocysteine levels does not affect the quality of oocytes. There is a positive correlation between the levels of homocysteine in the blood and follicular fluid in endometriosis group. [Indones J Obstet Gynecol 2013; 37-2: 92-8] Keywords: endometriosis, homocysteine, infertility, oocyte quality